A framework for mathematics inquiry-based classroom practice: the case of Célia. - Canavarro, Ana Paula (2013)
This paper has been developed in the context of the research project P3M Professional Practices of Mathematics Teachers. One of its main aims is to propose a framework for mathematics inquiry-based classroom practice, combining theoretical perspectives and the analysis of the teaching practice of experienced teachers that regularly conduct inquiry-based teaching of mathematics – in this paper, we focus on Célia case, a primary teacher teaching a 4th grade class. The framework adopts a four phases model for the lesson structure: 1) Introduction of the task; 2) Development of the task; 3) Discussion of the task; and 4) Systematization of the mathematical learning. For each phase, we describe the actions that the teacher intentionally performs with two main interrelated purposes: to promote the mathematical learning of the students and to manage the students and the class as a whole.